Apolipoprotein C‐II induces EMT to promote gastric cancer peritoneal metastasis via PI3K/AKT/mTOR pathway. Issue 8 (9th August 2021) - Wang, Chao; Yang, Zhi; Xu, En; Shen, Xiaofei; Wang, Xingzhou; Li, Zijian; Yu, Heng; Chen, Kai; Hu, Qiongyuan; Xia, Xuefeng; Liu, Song; Guan, Wenxian
Abstract: Background: Peritoneal metastasis (PM) occurs frequently in patients with gastric cancer (GC) and confers poor survival. Lipid metabolism acts as a non‐negligible regulator in epithelial–mesenchymal transition (EMT), which is crucial for the metastasis of GC. As apolipoprotein C2 (APOC2) is a key activator of lipoprotein lipase for triglyceride metabolism, the exact mechanism of APOC2 remains largely unknown in GC. Methods: Tandem mass tags identified differentially expressed proteins between human PM and GC tissues, and showed that APOC2 overexpressed in PM tissues, which was further confirmed by immunoblotting, immunohistochemistry, and ELISA. Global gene expression changes were identified in APOC2 knockdown cells via RNA‐sequencing. The role of APOC2 in lipid metabolism of GC cells was assessed via the Seahorse XF analyzer and lipid staining assays. The biological role of APOC2 in GC cells was determined by 3D Spheroid invasion, apoptosis, colony formation, wound healing, transwell assay, and mouse models. The interaction between APOC2 and CD36 was analyzed by co‐immunoprecipitation and biolayer interferometry. The underlying mechanisms were investigated using western blot technique. Results: APOC2 overexpressed in GC PM tissues. Upregulation of APOC2 correlated with a poor prognosis in GC patients. APOC2 promoted GC cell invasion, migration, and proliferation via CD36‐mediated PI3K/AKT/mTOR signaling activation. Furthermore, APOC2‐CD36 axis upregulated EMT markers of GC cells via increasing the phosphorylation of PI3K, AKT, and mTOR. Knockdown either APOC2 or CD36 inhibited the malignant phenotype of cancer cells, and delayed GC PM progression in murine GC models. Conclusion: APOC2 cooperates with CD36 to induce EMT to promote GC PM via PI3K/AKT/mTOR pathway. APOC2‐CD36 axis may be a potential target for the treatment of aggressive GC. Abstract : Tandem Mass Tags identified differentially expressed proteins (DEPs) between peritoneal metastasis (PM) and gastric cancer tissues, and showed that APOC2 was highly expressed in PM tissues. APOC2 cooperates with CD36 to regulate EMT process via PI3K/AKT/mTOR signaling, which eventually promotes tumor progression and peritoneal metastasis in gastric cancer.